The Costume Supervisor's Toolkit - Pride, Rebecca (Focal Press, 2019)
The Costume Supervisor's Toolkit explores the responsibilities of a Costume Supervisor within a theatrical, opera or dance production company. Rebecca Pride provides an insight into all manner of processes, beginning with a definition of the role, and offers explanations of the timeline from the first design meetings, leading all the way up to managing fittings and final rehearsals. This how-to guide outlines best working practices including building a team and creating a costume bible, whilst also providing helpful resources such as sizing guides, a list of useful addresses, and case studies from renowned theatrical organizations.